2015
DOI: 10.1007/s12603-015-0573-1
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory function, eating ability, and visceral obesity associated with MMSE three years after Parkinson's disease diagnosis

Abstract: This study indicates that olfactory function, cutting food, swallowing, and visceral obesity are associated with MMSE three years after PD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The use of shared neural substrates in the premotor frontal and orbitofrontal cortex by olfaction and cognition (Figure 2), and the contribution of cholinergic deficits to OD provides a potential mechanism for why greater OD appears to identify the subset of sporadic and monogenic PD patients at greater risk of future cognitive impairment [ (59,107,(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149); reviews: (27,150)]. Thus, genome-wide screens in PD subjects for variants that influence risk of severe OD or protect from developing OD may identify genetic factors that increase risk of, or offer protection from, cognitive impairment in PD.…”
Section: How Is Od Related To Disease Onset and Progression?mentioning
confidence: 99%
“…The use of shared neural substrates in the premotor frontal and orbitofrontal cortex by olfaction and cognition (Figure 2), and the contribution of cholinergic deficits to OD provides a potential mechanism for why greater OD appears to identify the subset of sporadic and monogenic PD patients at greater risk of future cognitive impairment [ (59,107,(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149); reviews: (27,150)]. Thus, genome-wide screens in PD subjects for variants that influence risk of severe OD or protect from developing OD may identify genetic factors that increase risk of, or offer protection from, cognitive impairment in PD.…”
Section: How Is Od Related To Disease Onset and Progression?mentioning
confidence: 99%
“…The clinical importance of hyposmia continues to evolve, and in individuals with PD olfaction testing can be used at a diagnostic tool [8] and is predictive of long-term cognitive decline and postoperative delirium [911]. In a large cohort of de novo patients, it was reported that PD patients with hyposmia exhibit more severe motor symptoms and required greater levodopa-equivalent at a 2.5-year followup compared to those patients with normal olfactory function [12].…”
Section: Introductionmentioning
confidence: 99%
“…Mini Nutritional Assessment is used for assessing the nutritional status of patients. There were 22 studies included in which MNA assessments were conducted [ 10 , 11 , 12 , 16 , 17 , 18 , 19 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. There was a total of 2713 participants, of which 39.2% were female and 60.8% were male.…”
Section: Resultsmentioning
confidence: 99%